2018
DOI: 10.1155/2018/6492143
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Randomness in Element Position on Performance of Communication Array Antennas in Internet of Things

Abstract: As a critical component for wireless communication, active phased array antennas face the restrictions of creating effective performance with the effect of randomness in the position of the array element, which are inevitably produced in the manufacturing and operating process of antenna. A new method for efficiently and effectively evaluating the statistic performance of antenna is presented, with consideration of randomness in element position. A coupled structural-electromagnetic statistic model for array a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Due to a variety of reasons including their small size, low cost, ease of deployment (deterministic or random) and simplified transmission-related protocols in terms of medium access channels and routing [3], it has been found that the antenna array is a key technology for a broad spectrum of future IoT applications ranging from weather forecasting or complex industrial plant monitoring to military surveillance [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a variety of reasons including their small size, low cost, ease of deployment (deterministic or random) and simplified transmission-related protocols in terms of medium access channels and routing [3], it has been found that the antenna array is a key technology for a broad spectrum of future IoT applications ranging from weather forecasting or complex industrial plant monitoring to military surveillance [4].…”
Section: Introductionmentioning
confidence: 99%
“…1. Random deployment whereas the sensors are randomly distributed over a specific area which collaboratively form an antenna array for beamforming purposes which is referred to as virtual random antenna array [4]. The location of each sensor must be considered on its own.…”
Section: Introductionmentioning
confidence: 99%
“…Also, antenna calibration quality is impaired by different measurement, and modelling errors such as signal-field distortions originated from non-planar wave-fronts, non-zero relative bandwidth (error or variance emanated from narrowband direction-of-arrival estimators when the sources have non-zero bandwidths), and parasitic reflections of calibration measurement surrounding. The influence of element position error on electromagnetic performance has been discussed and reported [4] using electromechanical coupling. Most literatures [4][5][6] concentrate on system failure with some corrective measures or its reliability and analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of element position error on electromagnetic performance has been discussed and reported [4] using electromechanical coupling. Most literatures [4][5][6] concentrate on system failure with some corrective measures or its reliability and analysis. However, little or no literature is openly accessible on the crucial failure-tolerant design aspects of an active spherical phased array for spacecraft applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation